Migrating to the cloud : oracle client/server modernization - Laszewski, Tom; Nauduri, Prakash (Syngress, 2012)
Whether your company is planning on database migration, desktop application migration, or has IT infrastructure consolidation projects, this book gives you all the resources you'll need. It gives you recommendations on tools, strategy and best practices and serves as a guide as you plan, determine effort and budget, design, execute and roll your modern Oracle system out to production. Focusing on Oracle grid relational database technology and Oracle Fusion Middleware as the target cloud-based architecture, your company can gain organizational efficiency, agility, increase innovation and reduce IT Total Cost of Ownership (TCO) by moving to service-oriented, Web-based cloud architectures. Focuses on Oracle architecture, Middleware and COTS business applications Explains the tools and technologies necessary for your legacy migration Gives useful information about various strategies, migration methodologies and efficient plans for executing migration projects